2013
DOI: 10.1007/s11284-013-1103-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulfur dioxide (SO2) on growth and physiological activity in Alnus sieboldiana at Miyakejima Island in Japan

Abstract: We used a physiological approach to investigate the effect of sulfur dioxide (SO2) on Alnus sieboldiana Matsum. (A. sieboldiana) and symbiotic Frankia spp. in Miyakejima Island, which was devastated by volcanic action in July of 2000. In April of 2008, three study sites were chosen in the forest of Miyakejima Island, and were categorized as high, medium, or low in relation to their sulfur dioxide concentration (volcanic gas). Nine A. sieboldiana trees were selected from naturally regenerated forest at each sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…In terms of C 3 plants, including trees, there are a few studies comparable to our data. Choi et al reported that the A max value for A. sieboldiana (an N-fixing C 3 tree species) at Miyake-jima Island [ 12 ], in a site with low exposure to the disturbances from the 2000 eruption, was 12 µmol·m −2 ·s −1 . This value is lower than that recorded for M. condensatus, even though the study site was highly disturbed and had low soil N. In the volcanically devastated site of Mt.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of C 3 plants, including trees, there are a few studies comparable to our data. Choi et al reported that the A max value for A. sieboldiana (an N-fixing C 3 tree species) at Miyake-jima Island [ 12 ], in a site with low exposure to the disturbances from the 2000 eruption, was 12 µmol·m −2 ·s −1 . This value is lower than that recorded for M. condensatus, even though the study site was highly disturbed and had low soil N. In the volcanically devastated site of Mt.…”
Section: Discussionmentioning
confidence: 99%
“…For example, altered root morphology, improved resource use efficiency, resorption efficiency (e.g., N, P), and N-fixing ability are all important adaptation strategies that allow plants to cope with poor nutrient habitats. Many studies have focused on N-fixing pioneer species at new volcanically devastated sites [ 9 , 10 , 11 , 12 ], because N is scarce in new volcanic materials, such as lava, scoria, and volcanic ash [ 2 ]. However, there are also many pioneer species without the N-fixing ability in volcanic succession.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average values of N area for F. japonica and A max for A. sieboldiana are even higher than the leaf traits from the N-rich habitat (Table A1). This reflects the relatively higher ability of these species to resist the N-low conditions in this volcanic environment; these plants also show an extremely low N requirement and demonstrate more effective N use strategies than the Miyake-jima pioneer species [11,39].…”
Section: Trait Comparison To Previous Studiesmentioning
confidence: 99%
“…Among these three species, A. sieboldiana (with N-fixing ability) can partially grow in volcanic N-deficiency deserts, as it has the ability to fix N in the atmosphere via symbiosis with nitrogen-fixers. Additionally, Choi et al [39] also proved its success in resisting high concentrations of volcanic gas (SO 2 ) in the Miyake-jima volcano. Regarding M. condensatus, our previous study [11] in the volcanically devastated site in Miyake-jima indicated that the relatively high light-saturated photosynthetic rate (A max ) and PNUE of M. condensatus were its adaptation advantages to volcanically N-deplete habitats.…”
Section: Introductionmentioning
confidence: 99%